Design and analysis of optical interconnection networks for a dataflow parallel computer - Perea Martins, João E.M. [UNESP]; Cavenaghi, Marcos A. [UNESP] (Springer Nature, 2008)
This work shows the design, simulation, and analysis of two optical interconnection networks for a Dataflow parallel computer architecture. To verify the optical interconnection network performance on the Dataflow architecture, we have analyzed the load balancing among the processors during the parallel programs executions. The load balancing is a very important parameter because it is directly associated to the dataflow parallelism degree. This article proves that optical interconnection networks designed with simple optical devices can provide efficiently the dataflow requirements of a high performance communication system. © Springer Science+Business Media B.V. 2008.